2014
DOI: 10.3390/rs6064741
|View full text |Cite
|
Sign up to set email alerts
|

Improving Species Diversity and Biomass Estimates of Tropical Dry Forests Using Airborne LiDAR

Abstract: The spatial distribution of plant diversity and biomass informs management decisions to maintain biodiversity and carbon stocks in tropical forests. Optical remotely sensed data is often used for supporting such activities; however, it is difficult to estimate these variables in areas of high biomass. New technologies, such as airborne LiDAR, have been used to overcome such limitations. LiDAR has been increasingly used to map carbon stocks in tropical forests, but has rarely been used to estimate plant species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 63 publications
2
34
1
7
Order By: Relevance
“…In addition to pulse density, performance of ALS based biomass estimation is also affected by the field plot size [16,41,42]. Combined effects of pulse density and plot size were assessed by Watt et al [16] who concluded that reduced pulse density and plot size had little effect on model fit for pulse densities >0.1 pulses·m and plot sizes of >0.03 ha.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pulse density, performance of ALS based biomass estimation is also affected by the field plot size [16,41,42]. Combined effects of pulse density and plot size were assessed by Watt et al [16] who concluded that reduced pulse density and plot size had little effect on model fit for pulse densities >0.1 pulses·m and plot sizes of >0.03 ha.…”
Section: Introductionmentioning
confidence: 99%
“…Both co-registration errors and boundary effects are reduced with reducing the ratio of field plot periphery to plot area. Accordingly, several studies on modelling of forest biomass using remotely sensed data have documented that increased plot size increased the model precision [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The 1-ha grid scheme and the horizontal precision of the 50-ha plot corners (0.050 m) helped to reduce co-registration errors related to misalignment between field subplots and LiDAR data, as well as plot-edge effects. There is a tendency for errors to decrease in biomass estimates with increasing plot size, because large plots reduce the likelihood of plot-edge effects, which occur when the canopy of trees are found along the plot boundary [21]. Edge effects are likely more pronounced in less dense stands and where plot sizes are smaller [56].…”
Section: Discussionmentioning
confidence: 99%